2010
DOI: 10.1211/jpp.62.05.0012
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective and antioxidant effects of gallic acid in paracetamol-induced liver damage in mice

Abstract: The results clearly demonstrate that gallic acid possesses promising hepatoprotective effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
81
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(91 citation statements)
references
References 32 publications
10
81
0
Order By: Relevance
“…Thus, this is in agreement with the works of Randle et al (2008) and Rasool et al (2010) who have reported elevations in serum transaminases (ALT and AST) after administration of high doses of paracetamol in Wistar albino rats. Due to the localization of these enzymes (ALT and AST), measurement of its activities in serum will give an indication of the status of the liver in disease conditions.…”
Section: Resultssupporting
confidence: 93%
“…Thus, this is in agreement with the works of Randle et al (2008) and Rasool et al (2010) who have reported elevations in serum transaminases (ALT and AST) after administration of high doses of paracetamol in Wistar albino rats. Due to the localization of these enzymes (ALT and AST), measurement of its activities in serum will give an indication of the status of the liver in disease conditions.…”
Section: Resultssupporting
confidence: 93%
“…The marked release of transaminases into the circulation is indicative of severe damage to hepatic tissue membranes during paracetamol intoxication [36]. This was consistent with the results of previous investigators who studied the effect of chronic paracetamol ingestion on liver damage [37].…”
Section: Discussionsupporting
confidence: 88%
“…There are several reports of this beneficial phytochemical for its potential antioxidant activity studied in animal models (2)(3)(4)(5)(6)(7). Other biological activities of GA studied in animal models are anticancer (1), antihyperglycemic (5), hepatoprotective (6), and antiviral (7) activity.…”
Section: Introductionmentioning
confidence: 99%